2019
DOI: 10.3390/ma12233999
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Measurements in Liquid Alloys and Phase Diagram Studies

Abstract: Towards the construction of pressure-dependent phase diagrams of binary alloy systems, both thermophysical measurements and thermodynamic modeling are employed. High-accuracy measurements of sound velocity, density, and electrical resistivity were performed for selected metallic elements from columns III to V and their alloys in the liquid phase. Sound velocity measurements were made using ultrasonic techniques, density measurements using the gamma radiation attenuation method, and electrical resistivity measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Ben Shalom et al reported the pressure diagram of the Ga-In system calculated with bulk thermodynamic data and highly accurate sound velocity and density data [ 56 ]. Similar works have been carried out for various systems, such as Bi-Sn [ 57 , 58 ], Bi-Sb [ 58 , 59 ], and Pb-Sn [ 58 , 59 ]. These studies demonstrate that this methodology can be applied to systems with high pressures of up to several GPa.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Ben Shalom et al reported the pressure diagram of the Ga-In system calculated with bulk thermodynamic data and highly accurate sound velocity and density data [ 56 ]. Similar works have been carried out for various systems, such as Bi-Sn [ 57 , 58 ], Bi-Sb [ 58 , 59 ], and Pb-Sn [ 58 , 59 ]. These studies demonstrate that this methodology can be applied to systems with high pressures of up to several GPa.…”
Section: Introductionmentioning
confidence: 77%
“… where is the bulk excess Gibbs energy under atmospheric pressure and is the excess volume, which can be expressed by Equation (24). where is the hypothetical volume of the alloy by ideal mixing, is the molar mass of the alloy, is the density of the alloy, is the molar mass of pure i , and is the density of pure i [ 56 , 57 , 58 , 59 ]. Here, it is assumed that the excess volume is constant at high pressures up to several GPa.…”
Section: Theory and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, techniques and methods for investigating material structures at the atomic level promote exceptional scientific results, leading to the development of advanced materials for all practical areas of interest (e.g., metallurgy, medicine, electronics, etc.) [21][22][23][24][25][26][27][28][29][30]. The phenomenology associated with quantities such as Gibbs' enthalpy, thermodynamic activity, entropy, free enthalpy, etc., must be seen from the perspective of material structure (phase stability analysis or phase transformations of an alloy system).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal analysis contributes to the calculation of phase diagrams (CALPHAD), both through experimental phase diagrams and by providing thermodynamic data for optimizations. Krishon et al [ 17 ] extend the CALPHAD approach by calculating pressure dependence of several binary metal phase diagrams based on the temperature dependence of sound velocity and density data in liquid alloys. Thus, this Special Issue provides a sampling of the current use, diversity, and ongoing developments of techniques and approaches in the thermal analysis of materials.…”
mentioning
confidence: 99%